Introduction to Social Work and Social Welfare - Charles Zastrow (Brooks/Cole-Thomson Learning, 2008)
Zastrow's comprehensive introduction to social work and social welfare looks at today's society with a realistic view of social problems and presents students with positive strategies in the context of the core values, ethics, skills and knowledge base of today's professional social worker. Zastrow provides solid content on both theory and practice skills, interwoven within the social problems context and encourages students to think about new and realistic ways to solve problems and empower clients. Cases, exhibits, and tables help apply concepts and also help students to compare and contrast the issues